A novel multidomain acyl-CoA carboxylase in Saccharopolyspora erythraea provides malonyl-CoA for de novo fatty acid biosynthesis - Livieri, Andrea L. (2019)
Fil: Fil: Livieri, Andrea L. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.